2018
DOI: 10.1158/0008-5472.can-17-2465
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Adipocyte/Macrophage Fatty Acid–Binding Protein in Tumor-Associated Macrophages Promotes Breast Cancer Progression

Abstract: Tumor-associated macrophages (TAM) play a critical role in cancer development and progression. However, the heterogeneity of TAM presents a major challenge to identify clinically relevant markers for protumor TAM. Here, we report that expression of adipocyte/macrophage fatty acid-binding protein (A-FABP) in TAM promotes breast cancer progression. Although upregulation of A-FABP was inversely associated with breast cancer survival, deficiency of A-FABP significantly reduced mammary tumor growth and metastasis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 48 publications
2
84
0
2
Order By: Relevance
“…Chemotherapy, the sole therapeutic route for TNBC patients, causes severe toxicity, resistance, and relapse; therefore, a better understanding of TNBC biology is needed. Mechanistic studies show strong links between adiposity, fatty acid metabolism, and BC risk [2][3][4][5], establishing a rationale for exploring related networks such as TNBC targets. Interest in the potential of the fatty acid binding protein (FABP) family, in particular, has recently been gaining traction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy, the sole therapeutic route for TNBC patients, causes severe toxicity, resistance, and relapse; therefore, a better understanding of TNBC biology is needed. Mechanistic studies show strong links between adiposity, fatty acid metabolism, and BC risk [2][3][4][5], establishing a rationale for exploring related networks such as TNBC targets. Interest in the potential of the fatty acid binding protein (FABP) family, in particular, has recently been gaining traction.…”
Section: Introductionmentioning
confidence: 99%
“…They activate transcription factors that are associated with proliferation, differentiation, and vascularization in multiple cancer types [8][9][10]. They may also act as mediators of cancer cell-stromal interactions [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggested that FABPs were associated with the development and progression of cancers [9][10][11]. A FABP inhibitor, BMS309403, was used to investigate if it could generate a similar effect to that seen in the berberinetreated cells.…”
Section: E Fabp Inhibitor Bms309403 Could Partially Recapitulate Thmentioning
confidence: 99%
“…FABPs, members of the superfamily of lipid-binding proteins, are key lipid metabolic enzymes responsible for the regulation of fatty acid uptake and intracellular transport [8]. It was reported that FABPs were closely associated with cancer development and were upregulated in many cancers such as renal cell carcinoma [9], hepatocellular carcinoma [10], and breast cancer [11], which indicates the potential role of FABPs as the tumor markers and therapeutic targets in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, A-FABP (also known as FABP4) is predominantly expressed in adipose tissue while epidermal FABP (E-FABP, FABP5) is the major FABP in the epidermis [3][4][5]. Our recent studies demonstrate that A-FABP expression in macrophages promotes protumour functions of tumour associated macrophages (TAM) in mouse models of breast cancer (BC) [6,7]. Moreover, A-FABP is secreted by adipose tissue to promote obesity-associated BC [8].…”
Section: Introductionmentioning
confidence: 99%